THE ROLE OF UZBEK MAQOM MUSIC IN THE INTERNATIONAL EDUCATION SYSTEM - Rashidov Sardor Alisher o‘g‘li; Qudratov Ismatilla (Innovate Conferences, 2025)
This scholarly article provides a comprehensive analysis of the role of Uzbek maqom music in the international education system. It highlights the unique artistic and philosophical characteristics of maqom, its recognition by UNESCO as intangible cultural heritage of humanity, and the growing interest from foreign researchers. The article examines the experiences of teaching maqom in foreign universities and conservatories, the contributions of Uzbek specialists, and the significance of online educational resources. Furthermore, it thoroughly discusses the methodological, linguistic, and financial challenges in teaching maqom internationally and offers well-founded recommendations for future expansion of international collaboration, creation of modern educational materials, and implementation of innovative teaching methods.
Keywords: status, international education, musical heritage, cultural integration, checkers, pedagogy, UNESCO